2022
DOI: 10.1039/d2tc04116b
|View full text |Cite
|
Sign up to set email alerts
|

Low dark current density in organic photodiodes achieved by reduced trap states of conjugated polymers bearing a fluorinated moiety

Abstract: A low dark current density (Jd) is critical for enhancing the performance of organic photodiodes (OPDs), which is evaluated by device parameters such as the signal-to-noise ratio, specific detectivity (D*),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…37−39 Bai et al found that in D-A-type CPs, fluorination of electron-donating units can suppress density of trap states in the active layer, effectively enhancing performance of OPDs. 40 Additionally, Park et al studied the effect of fluorinated alkyl chains in CPs on J dark and D* of OPDs. They found that introducing fluorine atoms into the alkyl side chains of CPs can improve their crystallinity and lower trap density and energy disorder, suppressing J dark and enhancing carrier mobility.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37−39 Bai et al found that in D-A-type CPs, fluorination of electron-donating units can suppress density of trap states in the active layer, effectively enhancing performance of OPDs. 40 Additionally, Park et al studied the effect of fluorinated alkyl chains in CPs on J dark and D* of OPDs. They found that introducing fluorine atoms into the alkyl side chains of CPs can improve their crystallinity and lower trap density and energy disorder, suppressing J dark and enhancing carrier mobility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Conjugated polymers (CPs) are an important component of bulk-heterojunctional OPDs in which structure modification of CPs can adjust their molecular aggregation, charge transport, and optoelectronic properties. CPs possess unique semiconductor properties, and understanding how to control their optoelectronic performance is critical for designing CPs with improved photoresponse characteristics. A large number of studies in the field of organic electronics show that the halogenation strategy is an ideal method to improve the optoelectronic properties of CPs. Fluorine (F) substitution, in particular, can not only adjust the energy level structure of CPs but also improve their crystallinity, trap density, and mobility. Bai et al found that in D-A-type CPs, fluorination of electron-donating units can suppress density of trap states in the active layer, effectively enhancing performance of OPDs . Additionally, Park et al studied the effect of fluorinated alkyl chains in CPs on J dark and D* of OPDs.…”
Section: Introductionmentioning
confidence: 99%